Mid-infrared optical and electrical properties of indium tin oxide films - Tamanai, Akemi; Sendner, Michael; Pucci, Annemarie (Physica status solidi. A, Applications and materials science, 2017)
Mid-infrared (MIR) optical properties of six various types of indium tin oxide (ITO) films have been investigated by means of infrared spectroscopic ellipsometry. We utilized both commercially available and uniquely fabricated ITO films which are composed of mainly two types of structures, “grain” and “grain-subgrain” having (200) and (400) preferential crystallographic orientations, respectively. For the determination of accurate dielectric properties of these ITO films, a thin surface layer on top of a bulk layer was considered for the spectral fits. These are done with a Drude model in the frequency range from 300 to 6000 cm−1. As a result of that, metallic behavior was verified in the MIR region for the surface and for the bulk layer. The real part of the complex dielectric function became increasingly negative toward low frequencies. The bulk layers form more than 70% of the total thickness of the films and have their plasma edges in the near-infrared. The optical properties of both surface and bulk layers strongly depend on the ITO fabrication conditions, which is enlightened by our study.